Green Supply Chain and Industry 4.0 Driven Carbon Neutrality Practices in Technologically Advanced Countries: A Circular Economy Perspective - Li, Yuanjian; Salman, Syed Muhammad; Altantsetseg, Purevdulam; Pardaev, Jamshid; Tien, Nguyen Hoang (Transformations In Business & Economics, 2026)
Global warming is a persistent challenge which needs wide-ranging solutions. Excessive reliance on non-renewable resources and industrialization has caused an increase in waste generation which calls for worthy strategies to reduce CO2 emissions by 2030 and meet zero carbon goal by 2050. Therefore, observing the relationship between green practices and circular economy is critical to address the carbon neutrality target. The present study scrutinizes how green logistics and artificial intelligence shape circular economy by considering factors such as economic growth, R&D, green taxes and renewable energy. The center focus of the study is technologically advanced economies covering the period from 2000 to 2023. The study employed Method of Moments Quantile Regression (MMQR) approach and reveals the artificial intelligence facilitates green logistics however, green logistics have no significance over circular practices in the given sample. Similarly, renewable resources and R&D have no direct impact on country’s economic growth, however, country’s growth and environmental taxes play major role in circular economy principles. To ensure robustness, the study also employed Feasible Generalized Least Square (FGLS) and validates the findings of MMQR. Given the scenario, the study encourages policy makers to show greater support to sustainable green logistic operations and AI- driven technologies in order to achieve carbon neutral goals.